Which patients with ES-SCLC are most likely to benefit from more aggressive radiotherapy: A secondary analysis of the Phase III CREST trial. (June 2017) - Slotman, Ben J.; Faivre-Finn, Corinne; van Tinteren, Harm; Keijser, Astrid; Praag, John; Knegjens, Joost; Hatton, Matthew; van Dam, Iris; van der Leest, Annija; Reymen, Bart; Stigt, Jos; Haslett, Kate; et al.
Highlights: Additional analysis of patients in CREST trial on Thoracic radiotherapy in ES-SCLC. OS and PFS were significantly better in patients with 2 or fewer metastases. OS was significantly worse if liver and/or bone metastases were present. Future studies on (extra)thoracic radiotherapy in ES-SCLC should focus on patients with 2 or fewer metastases. Abstract: Introduction: In ES-SCLC patients with residual intrathoracic disease after first-line chemotherapy, the addition of thoracic radiotherapy reduces the risk of intrathoracic recurrence, and improves 2-year survival. To identify patient subgroups for future trials investigating higher dose (extra)thoracic radiotherapy, we investigated the prognostic importance of number and sites of metastases in patients included in the CREST trial. Materials/ methods: Additional data on sites and numbers of metastases were collected from individual records of 260 patients from the top 9 recruiting centers in the randomized CREST trial (53% of 495 study patients), which compared thoracic radiotherapy (TRT) to no TRT in ES-SCLC patients after any response to chemotherapy. All patients received prophylactic cranial irradiation. Results: The clinical characteristics and outcomes of the 260 patients analyzed here did not differ significantly from that of the other 235 patients included in the CREST trial, except that fewer patients had a WHO = 0 performance status (24% vs 45%), and a higher proportion had WHO = 2 (15% vs 5%; p < 0.0001). No distant metastases were recorded in 5%, 39% had metastases confined to one organ, 34% to two, and 22% to three or more organ sites. Metastases were present in the liver (47%), bone (40%), lung (28%), extrathoracic (non-supraclavicular) lymph nodes (19%), supraclavicular nodes (18%), adrenals (17%) and other sites (12%). The OS (p = 0.02) and PFS (p = 0.04) were significantly better in patients with 2 or fewer metastases, with OS significantly worse if liver (p = 0.03) and/or bone metastases (p = 0.04) were present. Discussion: This analysis of patients recruited from the top 9 accruing centers in the CREST trial suggests that future studies evaluating more intensive thoracic and extra-thoracic radiotherapy in ES-SCLC should focus on patients with fewer than 3 distant metastases.